2020
DOI: 10.31557/apjcp.2020.21.6.1697
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Onset of Type 1 Diabetes Obtained from Real-World Data Analysis in Cancer Patients Treated with Immune Checkpoint Inhibitors

Abstract: Medications that target programmed cell death protein-1 (PD-1) have proven effective. However, blockade of PD-1/Programmed death-ligand 1(PD-L1) causes immune-related adverse events (irAEs). Characteristics of this irAE include many symptom, low in frequency, and difficulty in prevention. The key to a successful ICI-related treatment lies in the management of irAEs resulting from immune checkpoint inhibitor (ICI) treatment. Although it is difficult to predict irAE, we tried to extract features of irAE expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
1
9
1
Order By: Relevance
“…The prevalence of ICI-T1DM (0.8%) was close to that in the previous report by Stamatouli et al [20], in which the incidence was estimated to be 0.9%. The male predominance and tumor variance differed from the findings of Takada et al [10], who reported that female sex and having MM were risk factors for the development of ICI-T1DM.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The prevalence of ICI-T1DM (0.8%) was close to that in the previous report by Stamatouli et al [20], in which the incidence was estimated to be 0.9%. The male predominance and tumor variance differed from the findings of Takada et al [10], who reported that female sex and having MM were risk factors for the development of ICI-T1DM.…”
Section: Discussioncontrasting
confidence: 97%
“…As biomarkers of irAEs, Fujisawa et al [ 9 ] reported alterations in peripheral blood cell counts during irAEs. Regarding ICI-induced type 1 diabetes mellitus (ICI-T1DM), Takada et al [ 10 ] found that female sex and malignant melanoma (MM) were risk factors for ICI-T1DM. We have reported biomarkers [ 7 ] and the predisposing role of human leukocyte antigen (HLA) in thyroid dysfunction as an irAE [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of ADE reports for nivolumab is greater than those for the other ICPIs. Second, as a large spontaneous reporting system, the JADER database has various biases including under-or over-reporting and confounders caused by comorbidities (28, [41][42][43][44][45]. Third, the number of nephritis event was small in concomitant use of ICPI and PPI.…”
Section: Discussionmentioning
confidence: 99%
“…In general, women have a stronger immune response than men and are more likely to develop autoimmune diseases, which may be related to sex hormones and sex chromosome-related genes. 73 Takada et al 63 compared T1D irAEs with non-T1D irAEs using a real database of Japanese populations and found that being female and having melanoma were risk factors for T1D irAEs. Duma et al 64 studied the sex differences in irAEs between melanoma and NSCLC patients treated with PD-1 inhibitors, and the results suggested that premenopausal women with MM and women with NSCLC are prone to irAEs, pneumonia and endocrine toxicity.…”
Section: Population Characteristic Risk Factors For Iraesmentioning
confidence: 99%
“…Population characteristic risk factors provide important clues for clinicians and indicate which patients need to be monitored. Some researchers have found that female sex, age, smoking, and higher BMI were risk factors for irAEs, 28 , 63 , 64 , 68 , 72 but Kartolo et al 65 believed that these four factors were not related to irAEs. The tumor type in this study was mainly melanoma, while other studies mainly focused on NSCLC, and there were fewer subjects than in other studies.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%